PANDANGAN HAKIM TENTANG PENGATURAN PIDANA KERJA SOSIAL DI DALAM RUU KUHP DALAM SISTEM HUKUM PIDANA INDONESIA - SYAIFUDDIN, EDWIN (Dinamika Hukum, 2015)
This study aims at unearthing the concept of community service as a form of punishment in the updated Penal Code of Indonesia elaborated in the Draft Bill of Criminal Code Year 2013 and the views of judges on such arrangement within the Indonesian legal framework. Imprisonment as one form of sentences set out in Article 10 in the Criminal Code, especially inflicted on not-so-serious offences, has a loophole in that the purpose of sentencing is left unmet. The shift in the orientation for sentencing from being punitive to correctional drives the emergence of alternative to short term sentencing, namely community service punishment set out in the Draft Bill of Criminal Code which serves as a reform of the sentencing scheme prevailing in Indonesian legal framework. This study is juridical-sociological in nature. Involving interviews with judges, the study is conducted on the arrangement of social work punishment as set out in the Draft Bill of Criminal Code year 2013 compared with the punishments found in the existing Criminal Code. It provides descriptive analysis that presents and elaborates and then analyzes issues related to social work punishment, more particularly what served as the background for social work punishment arrangement and also the judges’ views on such arrangement. The concept of community service as a form of punishment outlined in the Draft Bill of 2013’s Criminal Code suggests an alternative to short term imprisonment or small fines. The arrangement of community service modernizes Indonesia’s substantive criminal law, by which judges are provided with an alternative when it comes to sentencing, for not all offences deserve imprisonment or sentences that deprive one from their liberty. Keywords: View of judges, Imprisonment, Draft Bill of Criminal Code, Community Service Punishment, Purpose of Sentence.